A survey of perceptions and behavioural responses towards the COVID-19 pandemic in South Africa - Takana M. Silubonde; Catherine E. Draper; Shane A. Norris (African Journal of Primary Health Care & Family Medicine)
Background: The South African response to the Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus was swift and assertive, although it came with economic and social costs. An understanding of the pandemic experiences of different population groups is integral to enhancing disease control.